Scope and Challenges of Islamic Finance in India - Bilal Ahmad Ganaie; Nasir Nabi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Islam and Islamic financial institutions hold an established and expanding presence within the Indian socio-economic landscape. India is reported to host more than 300 Islamic financial institutions, reflecting the commitment of the Muslim community to the principles of Shariah-compliant finance. The origins of Islamic finance in India can be traced to the 1890s with the creation of an interest-free lending initiative in southern India. Following independence, the sector witnessed notable growth, particularly during the 1960s, when numerous Islamic welfare societies primarily administered by Jamaat-e-Islami Hind, emerged across southern states, adhering to the core ideals of Islamic finance. By the late twentieth century, several Islamic financial investment companies, including Al-Baraka Finance House Limited (Mumbai), Seyad Shariat Finance Limited (Tamil Nadu), Al-Najib Milli Mutual Benefits Ltd. (Najibabad), and Parsoli Corporation Ltd., had become operational across both southern and northern India. These institutions aim to advance socio-economic welfare through principles rooted in justice, equity, and ethical financial conduct. This paper examines the potential and feasibility of Islamic financial institutions in advancing inclusive economic growth in India. It also analyses their relevance in addressing financial exclusion, poverty, debt cycles, unemployment, and wealth disparities, while identifying key regulatory challenges and suggesting pathways for effective integration into the national financial system.